2007
DOI: 10.1002/chir.20449
|View full text |Cite
|
Sign up to set email alerts
|

Chiral NMR discrimination of amines: Analysis of secondary, tertiary, and prochiral amines using (18‐crown‐6)‐2,3,11,12‐tetracarboxylic acid

Abstract: Enantiomeric discrimination is observed in the 1H and 13C NMR spectra of secondary and tertiary amines in the presence of (-)-(18-crown-6)-2,3,11,12-tetracarboxylic acid (1). Nonequivalence of the resonances of prochiral nuclei in primary and secondary amines is also observed when they associate with 1. The amines are added in their neutral form and are protonated by the carboxylic acid groups of 1 to produce the corresponding ammonium and carboxylate ions. Secondary amines associate with 1 through two hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The crown ether (18-crown-6)-2,3,11,12-tetracarboxylic acid has been used in water as a chiral solvating agent for primary amines, 30 although the enantiomeric discrimination with this crown ether is better in methanol and acetonitrile. [30][31][32][33][34][35][36][37][38] Calixarenes and calix [4]resorcinarenes are two other important families of cavity compounds, [39][40][41][42] although these have found limited application in NMR spectro-scopy. 1,[43][44][45][46][47][48][49][50][51] One exception is a tetrasulfonated calix [4] resorcinarene that contains optically pure L-prolinylmethyl groups (1).…”
Section: Introductionmentioning
confidence: 99%
“…The crown ether (18-crown-6)-2,3,11,12-tetracarboxylic acid has been used in water as a chiral solvating agent for primary amines, 30 although the enantiomeric discrimination with this crown ether is better in methanol and acetonitrile. [30][31][32][33][34][35][36][37][38] Calixarenes and calix [4]resorcinarenes are two other important families of cavity compounds, [39][40][41][42] although these have found limited application in NMR spectro-scopy. 1,[43][44][45][46][47][48][49][50][51] One exception is a tetrasulfonated calix [4] resorcinarene that contains optically pure L-prolinylmethyl groups (1).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, secondary amino compounds were proposed to be resolved on CSP 1 through the ionic interaction between the cationic site of the protonated secondary amines and anionic carboxylate group of the CSP and the two N–H + ···O hydrogen bonds between the secondary ammonium ions (RR′‐NH 2 + ) and the crown ether ring of the CSP as shown in Figure A . The ionic interaction shown in Figure A has also been proposed from NMR spectroscopy of the recognition of secondary amines using (+)‐(18‐crown‐6)‐2,3,11,12‐tetracarboxylic acid as a NMR chiral solvating agent . The identical chiral recognition mechanism might be applied to the resolution of methoxyphenamine ( 3 ) on CSP 2 as shown in Figure B.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies with x-ray crystallography and nuclear magnetic resonance spectroscopy have demonstrated the affinity of 18c6H 4 for protonated amines, amino acids, amino alcohols and further compounds with free amino functionality. [8][9][10][11][12][13][14][15][16] Those studies have provided evidence for the relevance of the barrel-like and bowl-like structures adopted by 18c6H 4 . Such structures are sustained by intramolecular H-bonding involving the carboxyl groups and by intermolecular interactions of the cationic guest with the ether and carboxyl oxygen atoms.…”
Section: Introductionmentioning
confidence: 86%